Forecasting and probability analysis of rainfall in Varanasi of Uttar Pradesh - MISHRA, P.; PARIHAR, S. S.; TRIPATHI, S. K.; SAHU, P. K. (Journal of Soil and Water Conservation, 2021)
The time series rainfall data for the period of 29 years (1981-2009) of Varanasi agro-climatic zone of Uttar Pradesh were analyzed to know monthly, seasonal and annual probabilities at different levels of rainfall for suitable crop planning. This study aims at studying the rainfall distribution characteristics of Varanasi, by using different statistical analyses continuous distributions. Normal annual rainfall of the area was 1000.97 mm. Coefficient of variation of rainfall for kharif, rabi, and zaid season are 24.79%, 55.29% and 80.04%, respectively. The best fit probability distribution of monthly data was found to be different for each month. This study also focuses on forecasting the annual rainfall in Varanasi using Autoregressive Integrated Moving Average (ARIMA) model. The analyses forecast annual rainfall for the year 2020 to be about 742.12 mm. Such knowledge of rainfall pattern and its distribution for any area, particularly under rainfed condition, will help in crop planning vis-a-vis crop productivity of the area concerned.